Evolution of genome-wide barriers to gene flow during complex speciation in rattlesnakes - Keaka Farleigh; Dylan K. Highland; Megan G. Alderman; Yannick Francioli; Samuel R. Hirst; Ellie M. Faber; Blair W. Perry; Matthew L. Holding; Gamaliel Castañeda-Gaytán; Miguel Borja; Hector Franz-Chávez; Christopher L. Parkinson; et al. (Proceedings of the National Academy of Sciences, 2026)
Speciation with gene flow poses a central paradox: how do genome-wide barriers to gene exchange accumulate as recombination continually breaks down associations among selected loci? Although theory predicts that together recombination, selection, and genome structure shape reproductive isolation, empirical studies often report conflicting patterns, suggesting that these determinants change across the speciation continuum. Here we compare genomic landscapes of introgression across rattlesnake lineages spanning a range of divergence. We generated a chromosome-level reference genome for the Southwestern Speckled Rattlesnake ( Crotalus pyrrhus ) and analyzed whole genome data from 181 individuals across two species complexes with a history of gene flow upon secondary contact. We show that reproductive isolation is highly polygenic and dynamically structured. At early divergence, introgression is most reduced in high recombination regions, consistent with increased efficacy of selection against gene flow at few large-effect loci. As divergence progresses, linked selection against gene flow dominates, generating a positive relationship between recombination and introgression expected to occur through the genome-wide coupling of polygenic barrier effects. Introgression landscapes also become increasingly correlated across species pairs as divergence increases due to repeated evolution of barriers in the same genomic regions. Here, we infer that the Z chromosome plays a prominent role in reproductive isolation, harboring a disproportionate number of barrier loci and showing reduced introgression even at early divergence. Together, these results reveal how recombination, selection, and genome organization interact to shape speciation with gene flow upon secondary contact, reconciling empirical patterns with predictions of speciation theory.